EKONOMI POLITIK DAN PERAN SEKTOR PUBLIK “Peran Pemerintah dalam Mengatasi Kegagalan Mekanisme Pasar” - Reres Agustin (Faculty of Economics and Business, Jenderal Soedirman University, 2021)
Along with the times, of course, the economic success of a country is influenced by several factors that support it. One of them is in the field of political economy. However, along with these developments, the economic system encountered several obstacles, such as the failure of the market mechanism. Political economy and its own tools are involved in overcoming this failure. The government's role in the failure of this market mechanism is needed to stabilize a country's economy and provide justice for economic actors. The purpose of this journal is to find out what the relationship between political economy and the public sector is, by discussing in detail the role of government in overcoming the failure of market mechanisms. The source of the data we obtained comes from a collection of various information obtained through the media of literature and readings that refer to the title of the discussion of political economy and the role of the public sector.